Caribbean Basin : mechanisms to enhance the participation of the social actors in the regionalization process - Ossa, Alvaro de la (SELA CaracasVE, 1996)
Considers some bases which may serve to promote regionalization. Focuses on factors that should be taken into account to determine the most suitable mechanisms for strengthening intra-Basin regionalization. Analyses the procedures which have been followed in the Central American isthmus to establish a link between the social actors and the governments as far as the policy of multilateraliztion is concerned. Presents conclusions and proposals.